Tratamiento contable y financiero de la aplicación de la sección 13 para pymes en Colombia. (2020)
The objective of this reflective article is to identify the accounting and financial treatment of inventories under IFRS with reference to section 13 in small and medium sized companies in Colombia, which frame a series of guidelines and methods to be followed in the manner in which the information is presented in the financial statements. To this end, we seek to analyze a series of changes produced by the accounting application process in terms of recognition, measurement, trade discounts and to understand the importance of the inventory in the cash flow of an SME in Colombia, as the new international accounting frameworks have been gradually applied, which are the IFRS (international financial reporting standards), which seek to disclose financial information in a uniform manner throughout the world to facilitate its interpretation in a global manner.